Chemical constituents from Cremanthodium brunneo-pilosum S. W. Liu. (August 2015) - He, Zhi-Zhou; Ding, Li-Sheng; Xu, Rui-Hong; Wan, Bo; Peng, Shu-Lin; Liu, Hao-Huai; Zeng, Yuan
Abstract: Fourteen compounds were isolated from Cremanthodium brunneo-pilosum, including two steroids (1 and14 ), five sesquiterpenoids (2–6 ), six flavonoids (7–12 ) and one isoflavone (13 ). Graveolide (2 ) was obtained from a plant for the first time. 5, 7-Dihydroxy-3, 6, 3′, 4′-tetramethoxy-flavone (9 ), centaureidin (10 ) and tectoridin (13 ) have not been isolated from the family Compositae. The chemotaxonomic data support the relationship between this species and others in the family Compositae. Highlights: Fourteen compounds were firstly isolated from Cremanthodium brunneo-pilosum. Sesquiterpenoids could be used as chemotaxonomic markers of Cremanthodium brunneo-pilosum. Cremanthodium is in a lower position in the evolutionary advancement of Compositae.